Multiobjective Synthesis of Steerable UWB Circular Antenna Array considering Energy Patterns - Leopoldo A. Garza; Marco A. Panduro; David H. Covarrubias; Alberto Reyna (International Journal of Antennas and Propagation)
True-time delay antenna arrays have gained a prominent attention in ultrawideband (UWB) applications such as directional communications and radar. This paper presents the design of steerable UWB circular array by using a multiobjective time-domain synthesis of energy pattern for circular antenna arrays. By this way we avoid individual beamforming for each frequency in UWB spectrum if the problem was addressed from the frequency domain. In order to obtain an energy pattern with low side lobe level and a desired main beam, the synthesis presented is performed by optimizing the true-time delays and amplitude coefficients for the antenna elements in a circular geometry. The method of Differential Evolution for Multiobjective Optimization (DEMO) is used as the optimization algorithm in this work. This design of steerable UWB circular arrays considers the optimization of the true-time exciting delays and the amplitude coefficients across the antenna elements to operate with optimal performance in the whole azimuth plane (360°). A comparative analysis of the performance of the optimized design with the case of conventional progressive delay excitations is achieved. The provided results show a good performance for energy patterns and for their respective power patterns in the UWB spectrum.